2016
DOI: 10.22256/pubvet.v10n11.855-860
|View full text |Cite
|
Sign up to set email alerts
|

Relação temperatura e nutrição sobre o desempenho de galinhas poedeiras

Abstract: RESUMO.Aves são animais homeotérmicos, e devido a isso conseguem manter a temperatura corporal relativamente constante, independente da temperatura ambiental em que estão inseridas, desde que a amplitude em que se encontra a zona de conforto térmico seja respeitada. A ótima produtividade de poedeiras depende do conjunto de medidas que atendam às necessidades dos animais em nutrição, sanidade, genética e bem-estar. Por ser um animal homeotérmico, a temperatura do ambiente é um parâmetro avaliado relacionado ao … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…Because feathers can work as a thermal insulating agent and promote an increase in body temperature (Melo et al, 2016), their reduction may favor body heat dissipation and reduce the negative influence of high ambient temperatures, as observed by Santos et al (2012a). Those authors found lower variations in cloacal temperature in Naked Neck chicks as compared with featherless birds, which reduced stress from high temperatures and favored production indices.…”
Section: Resultsmentioning
confidence: 93%
“…Because feathers can work as a thermal insulating agent and promote an increase in body temperature (Melo et al, 2016), their reduction may favor body heat dissipation and reduce the negative influence of high ambient temperatures, as observed by Santos et al (2012a). Those authors found lower variations in cloacal temperature in Naked Neck chicks as compared with featherless birds, which reduced stress from high temperatures and favored production indices.…”
Section: Resultsmentioning
confidence: 93%
“…As galinhas poedeiras são animais homeotérmicos, dotadas de pena em volta do corpo, favorecendo o isolamento térmico e dificultando a troca de calor com o meio (Melo et al, 2016). As aves não apresentam glândulas sudoríparas e possuem baixa capacidade de troca térmica na forma latente, sendo o seu sistema termorregulador mais adequado para reter calor do que para dissipar (Teixeira e Baião, 2012).…”
Section: Resultsunclassified
“…Existe uma relação entre a temperatura e a nutrição que deve ser analisada, pois a temperatura ambiente regula principalmente o consumo de alimentos, podendo levar a reações que afetam negativamente a nutrição da ave, o que acaba prejudicando o peso corporal e a maturidade sexual (Melo et al, 2016).…”
Section: Variáveisunclassified
“…In regions where high temperatures predominate, the zootechnical farming of several animal species is impaired, especially broilers, which have a deficient thermoregulatory system (MELO et al, 2016). In this scenario, birds perform a series of behavioral and physiological changes that culminate in decreased productivity.…”
Section: Introductionmentioning
confidence: 99%